Abnormal cerebellar functional MRI connectivity in patients with paediatric multiple sclerosis. (March 2016) - Cirillo, Sara; Rocca, Maria A; Ghezzi, Angelo; Valsasina, Paola; Moiola, Lucia; Veggiotti, Pierangelo; Amato, Maria P; Comi, Giancarlo; Falini, Andrea; Filippi, Massimo
Objectives: We investigated resting state functional connectivity (RSFC) of the cerebellar dentate nuclei in paediatric MS patients and its correlations with clinical, neuropsychological and structural MRI measures. Methods: RSFC analysis was performed using a seed-region correlation approach and SPM8 from 48 paediatric MS patients and 27 matched healthy controls. Results: In both groups, dentate nuclei RSFC was significantly correlated with RSFC of several cerebellar and extra-cerebellar brain regions. Compared with healthy controls, paediatric MS patients had reduced RSFC between the right dentate nuclei and the bilateral caudate nuclei and left thalamus as well as increased RSFC between the right dentate nuclei and the left precentral and postcentral gyri. Cognitively impaired patients showed a reduced RSFC between the dentate nuclei and bilateral regions located in the parietal, frontal and temporal lobes. Decreased RSFC was correlated with longer disease duration and higher T2 lesion volumes, whereas increased RSFC correlated with shorter disease duration, lower T2 lesion volume and a better motor performance. Conclusions: Modifications of cerebellar RSFC occur in paediatric MS and are influenced by the duration of the disease and brain focal lesions. Decreased RSFC may reflect early maladaptive plasticity contributing to cognitive impairment.